Enhancing Organizational Agility through Knowledge Management: The Role of English Proficiency in Multinational Teams - Pramesti, Puji (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
This study examines the interplay between English proficiency, knowledge management (KM) practices, and organizational agility in multinational teams. Drawing on data from surveys and interviews conducted across industries such as Information Technology, Financial Services, and Management Consulting, the research identifies key correlations between these variables. The findings reveal that higher English proficiency reduces language barriers, enabling more effective KM practices, which in turn enhance organizational agility. Additionally, industries that emphasize knowledge-intensive operations benefit significantly from integrating language training and KM strategies. The study underscores the importance of fostering a collaborative, knowledge-sharing culture to optimize team performance and adapt to dynamic global markets.